Rzeczpospolita Niepodległa [banknot podziemny] . The Independent Republic. Unofficial bank note - Niezależny Bank Polski. (Niezależny Bank Polski, 1984)
Double-sided b&w and green print on white paper. Banknote, with the portrait of Józef Piłsudski (obverse) and Warsaw Cytadel (reverse), resembles a US dollar. Attributes of the banknote include: series, number and date of emission, signature of the director of emitting agency, and watermark. Images on obverse and reverse bear explanatory captions. Denomination: 250 zł.